Percepatan Penyediaan Benih Sumber Kedelai Unggul Secara In Vitro - Erni Suminar; Sumadi Sumadi; Syariful Mubarok; Toto Sunarto; Nita Suswati Endah Rini (Agrikultura, 2017)
ABSTRACTIn vitro method to fasten availability high quality soybean seedsSoybean is an important crop as a source of food and its demand has increased every year. Several new varieties of soybean have been generated, but the number is still limited. Furthermore, the infestation of pests and infection of diseases have also limited the new soybean varieties production as it increase the risk of growth failure. Therefore, methods to fasten the availability of high quality of soybean seeds need to be developed. One of which can be done through in vitro culture method. The objective of this study was to obtain the best type and the best concentration of cytokinin for the growth of soybean explants in vitro. The experiment was conducted in Seed Technology and Tissue Technology Laboratory, Faculty of Agriculture, Universitas Padjadjaran. The experimental design used was Completely Randomized Design with 13 treatments and four replications. The basic media used were Murashige and Skoog (MS) + Vitamin B5 with addition of BAP (1.0 mg/l, 1.5 mg/l, and 2.0 mg/l), Kinetin (0.5 mg/l, 1.0 mg/l, and 1.5 mg/l), TDZ (0.01 mg/l, 0.1 mg/l, and 1.0 mg/l), and coconut water (10%, 15%, and 20%). The result showed that cytokinin types and concentrations gave different effect to soybean explant growth. The best treatment was demonstrated by BAP at the concentration of 1.5 mg/l as shown by the highest percentage of leaves and the number of shoots. However, it did not affect the percentage of buds produced by explant and the percentage of callus produced by explant.Keyword : BAP, Kinetin, TDZ, Coconut water, Soybean.AbstrakKedelai merupakan komoditas yang memegang peranan penting. Permintaan akan kedelai meningkat setiap tahunnya. Varietas kedelai baru yang bersifat unggul sudah banyak dihasilkan, namun jumlahnya masih terbatas. Tingginya serangan hama dan penyakit saat perbanyakkan benih di lapangan menyebabkan tingginya resiko kegagalan dalam pertumbuhan varietas baru tersebut. Sehingga perlu dilakukan percepatan penyediaan benih sumber varietas unggul di laboratorium secara in vitro. Tujuan penelitian ini adalah untuk mendapatkan jenis dan konsentrasi sitokinin yang terbaik untuk pertumbuhan eksplan kedelai in vitro. Penelitian dilakukan di Laboratorium Kultur Jaringan Teknologi Benih Fakultas Pertanian Universitas Padjadjaran. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap dengan tiga belas perlakuan dan empat ulangan. Media dasar yang digunakan adalah Murashige dan Skoog (MS) + Vitamin B5 dengan penambahan BAP (1,0 mg/l; 1,5 mg/l; 2,0 mg/l), Kinetin (0,5 mg/l; 1,0 mg/l; 1,5 mg/l), TDZ (0,01 mg/l; 0,1 mg/l; 1,0 mg/l), dan air kelapa (10%; 15%; 20%). Hasil percobaan menunjukkan bahwa pemberian jenis dan konsentrasi sitokinin memberikan pengaruh yang berbeda terhadap pertumbuhan eksplan. Perlakuan terbaik diperoleh pada BAP dengankonsentrasi 1,5 mg/l yang ditunjukkan dengan tingginya persentase jumlah daun dan tunas yang terbentuk. Akan tetapi, penambahan sitokinin tersebut tidak memberikan pengaruh terhadap persentase eksplan dalam membentuk tunas dan persentase eksplan dalam membentuk kalus.Kata Kunci : BAP, Kinetin, TDZ, Air Kelapa, Kedelai